An integrated CMOS voltage multiplier and shunt voltage regulator of RF energy harvester for health care monitoring system - Zulkifli F.F.; Sampe J.; Islam M.S.; Rhazali Z.A. (Asian Network for Scientific Information, 2023)
Background: The increasing demand of energy harvester implementation in low power electronic devices has encouraged most of the researchers to put more effort to improve the efficiency and sensitivity of RF energy harvester system. Materials and Methods: In this study, these three blocks; voltage boosting and matching network, voltage multiplier and voltage regulator have been combined to harvest RF input as low as -20 dBm at operating frequency 915 MHz. By designing a network at the beginning of the circuit which called as voltage boosting network, the low input signal is boosted to sufficient voltage that can switch on the active component of voltage multiplier such as MOSFET. This network is designed based on LC resonant circuit which is consists of inductor and capacitor. Meanwhile, voltage multiplier is designed based on Dickson's voltage multiplier concept which utilizing NMOS diode with bulk modulation technique. The purpose of this technique is to lower down the threshold voltage (Vth)of the MOSFET. By using this four stages voltage multiplier, the input AC voltage has been rectified and boosted up efficiently. This circuit is designed based on 0.13 ?m CMOS technology. Results: This system managed to achieve approximately 2 V at -10 dBm input power for 1 M? load resistance. However, to avoid over voltage to the load, a voltage regulator based on zener diode that is applied to limit and regulate the output voltage of rectifier. The key finding of this study is the system able to produce 2.72 V for -8 dBm input power at resistance load 1 M? and the efficiency about 30.95% which is much better compared to previous study. Conclusion: The proposed combination blocks of LC circuit, voltage multiplier and voltage regulator is able to produce suitable voltage for helath care monitoring system applications. 2016 Farah Fatin Zulkifli et al.